Efficacy of polyprenyl phosphates in the experimental genital herpes model - A. N. Narovlyansky; А. M. Ivanova; N. V. Shevlyagina; L. V. Didenko; Т. G. Borovaya; А. V. Izmest’eva; А. V. Sanin; А. V. Pronin; F. I. Ershov (Вопросы вирусологии, 2015)
An experimental model of the primary genital herpes (herpes simplex type 2, HSV-2) in the female guinea pigs was suggested to study the infectious process activity of polyprenyl phosphates (PPP) and PPP+acyclovir (AC) complex treatment. The morphofunctional features of the guinea pig ovaries were studied in the control and experimental groups (the latter were inoculated with PPP and/or AC as a primary infection treatment) at the stage of the recurrent genital herpes aggravation. It was shown that in the case of combined PPP +AC use significant changes in the disease symptoms were observed, as well as a decrease in the infectious process activity and duration, and positive remote effect on the ovarian morphophysiology.